2020
DOI: 10.1182/blood.2020005125
|View full text |Cite|
|
Sign up to set email alerts
|

Thrombosis in patients with myeloma treated in the Myeloma IX and Myeloma XI phase 3 randomized controlled trials

Abstract: Newly diagnosed multiple myeloma (NDMM) patients treated with immunomodulatory drugs (IMiDs) are at high venous thrombosis (VTE) risk, but data are lacking from large prospective cohorts. We present thrombosis outcome data from Myeloma IX (n=1936) and Myeloma XI (n=4358), phase III randomized controlled trials for NDMM, treating transplant-eligible and ineligible patients before and after publication of thrombosis prevention guidelines. In Myeloma IX, compared to CTD (cyclophosphamide, thalidomide and dexameth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 39 publications
2
69
1
2
Order By: Relevance
“…30,31 In newly diagnosed multiple myeloma, the VTE rate is estimated to be at least 10% with the majority of events occurring in the first 6 months of induction. 32 A systematic review of 6 studies, encompassing 1125 patients receiving lenalidomidebased therapy, demonstrated a 10.7% total risk of VTE with aspirin compared with 1.4% with LMWH in multiple myeloma patients. 33 More evidence is needed to determine the best strategy to reduce the risk of arterial and venous thrombosis in myeloma patients starting immunomodulatory drugs.…”
Section: Primary Vte Prevention In Selected Medical Populationsmentioning
confidence: 99%
“…30,31 In newly diagnosed multiple myeloma, the VTE rate is estimated to be at least 10% with the majority of events occurring in the first 6 months of induction. 32 A systematic review of 6 studies, encompassing 1125 patients receiving lenalidomidebased therapy, demonstrated a 10.7% total risk of VTE with aspirin compared with 1.4% with LMWH in multiple myeloma patients. 33 More evidence is needed to determine the best strategy to reduce the risk of arterial and venous thrombosis in myeloma patients starting immunomodulatory drugs.…”
Section: Primary Vte Prevention In Selected Medical Populationsmentioning
confidence: 99%
“…A retrospective French study conducted on 236 patients treated with an IMiDs-based regimen demonstrated that only 43% high-risk and 34% low-risk patients received a thrombo-prophylaxis [19]. Another study evaluated 80 MM cases with treatment-related VTE with 85% of them classified as high risk, but only 19% had received an appropriate prophylaxis according to IMWG [50]. The failure to adhere to the recommendations of the guidelines was also recorded in the context of controlled clinical studies: the English study Myeloma XI included treatment with IMiDs at diagnosis, an assessment of the thrombotic risk in accordance with the IMWG guidelines and consequently a prophylaxis with LMWH for high risk patients and with ASA for low risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…The failure to adhere to the recommendations of the guidelines was also recorded in the context of controlled clinical studies: the English study Myeloma XI included treatment with IMiDs at diagnosis, an assessment of the thrombotic risk in accordance with the IMWG guidelines and consequently a prophylaxis with LMWH for high risk patients and with ASA for low risk patients. Despite these recommendations, almost 20% of patients did not receive any prophylaxis and 23% of patients classified as high risk underwent prophylaxis with ASA rather than LMWH [ 50 ]. A recent review has confirmed that ASA was the most frequent prophylaxis in patients treated with lenalidomide, no matter the individual risk assessment [ 44 ] and the most recent guidelines from NICE (National Institute for Health and Care Excellence) suggest that in patients with myeloma who are receiving treatment with thalidomide, lenalidomide or pomalidomide and steroids, it is possible to choose either aspirin or prophylactic dose of LMWH (NICE 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite extensive use of systemic anticoagulants thromboembolic events remain a problem particularly in IMiD-treated patients. 84 Happily, despite the trend to ever more intensive therapy quality of life does not appear to be adversely affected. 22,85 Longer survivals have meant that extra-medullary disease (EMD) is seen more often, usually as a late finding, often containing a new clone of the disease, and these progressions are frequently difficult to manage.…”
Section: Supportive Carementioning
confidence: 99%